Intensification of storm water treatment of wood transferring wood termination facilities - Svetlana B. Kundenok; Vladislava N. Volkova (RUDN Journal of Ecology and Life Safety)
The study presents the individual technology developed by the authors for the collection and disposal of surface runoff from the facilities of the port complex for the transshipment of wood chips in the conditions of the existing port infrastructure. An analysis of the project implementation was carried out. An innovative coagulating composition has been developed that reduces the desalination of sea water, and design solutions have been developed to intensify the operation of treatment facilities. The technological solutions proposed by the authors can be applied in the design of storm sewerage for berth structures and wastewater treatment.